Evaluation of oxygen surface potential at early stage of oxidation in dry and water vapor condition at 1073 K - Ani, Mohd Hanafi; Ueda, Mitsutoshi; Kawamura, Kenichi; Maruyama, Toshio (2010)
Hanafi [1] and Asep [2] et. al. have shown that the presence of water vapor in oxidation environment enhances the oxygen transport along the precipitates oxide/metal interface. This explains the reason of accelerated oxidation rates and anomalous oxidation behavior in water vapor condition. Oxygen potential on the surface of oxide during the oxidation is a subject of interest which may explains the formation of oxides at early stage. Akiba [3] et. al. have successfully monitor the oxygen chemical potential on growing oxide scales during the oxidation of Fe, Ni and Co at 1373 K. Slight modification of the oxygen sensor from Akiba’s work was made and the oxygen chemical potential on oxide of Fe-Cr alloys was measured. The objective of this study is to clarify the change on surface oxygen potential during oxidation of Fe-Cr alloy in water vapor condition.